Structural behaviour of pre-damaged RC columns immediate repaired employing pre-tensioned steel straps. (December 2021) - Apandi, Nazirah; Ma, Chau-Khun; Awang, Abdullah Zawawi; Omar, Wahid
Abstract: Research focusing on the effects of pre-damaged level on the effectiveness of concrete repairing using external confinement is quite limited. In addition, the use of active confinement in concrete repair works is yet to be explored. This study extends the investigation on repairing reinforced concrete (RC) columns to the active-typed confinement. Experimental tests were conducted to investigate the applicability of active confinement in repairing RC columns with varied pre-damaged levels. The applicability of steel strapping confinement in repairing RC columns with the varied pre-damaged levels was confirmed through experimental works, which involved testing of 21 RC columns under monotonic uniaxial compression. The overall responses of the specimens were investigated in terms of crack pattern, load carrying capacity, axial displacement, stiffness and ductility of repaired columns. The test results have shown that the restorability of confinement was significantly affected by pre-damaged levels. It is also observed that the increase in confining volumetric ratio can restore both strength and ductility of repaired RC columns up to 171% and 172%, for the same pre-damaged level.